Social engineering in the company management - Gajda, Waldemar; Zaczyńska vel Zaczek, Joanna (Economy Today: An Interdisciplinary Approach to Contemporary Economic Challenges, 2016)
Purpose: The aim of this article is to indicate opportunities for the practical use of social engineering in the company management. Design/methodology/approach: The method of analysis and idiographic method were used as research methods. The latter enables the acquisition of information which reveals unusual, distinct, unique and distinguishing features of a phenomenon of social engineering operations. Findings: The first part of the article is a presentation of social engineering as science with specification of its origin and scientific interpretation disputes. The methodological bases of social engineering were specified. The rules and methods as well as basic social engineering models were indicated. Subsequently, having conducted an analysis of opportunities for the use of social engineering, features of social engineering which qualify it to the group of practical sciences were indicated. The second part of the article constitutes the transmission of scientific considerations into the practical use of social engineering in business entities management. The use of social engineering in relation to an individual and groups of employees in order to form adequate attitudes in a company and the opportunities of its practical exploitation to solve problems are indicated. Research limitations/implications: The use of social engineering which is presented in the article does not exhaust the problem and does not constitute any remedy. It is only an attempt of indication of opportunities of the use of this science and an impulse to further studies regarding its effective implementation in company management. Original value: The connection between a theory of science on social engineering and its practical use in the management of a company through the formation of adequate attitudes of both an individual and groups of employees in a company.